Look-ahead approaches for integrated planning in public transportation - Pätzold, Julius; Schiewe, Alexander; Schiewe, Philine; Schöbel, Anita (OpenAccess Series in Informatics, 2017)
In this paper we deal with three consecutive planning stages in public transportation: Line planning (including line pool generation), timetabling, and vehicle scheduling. These three steps are traditionally performed one after another in a sequential way often leading to high costs in the (last) vehicle scheduling stage. In this paper we propose three different ways to "look ahead", i.e., to include aspects of vehicle scheduling already earlier in the sequential process: an adapted line pool generation algorithm, a new cost structure for line planning, and a reordering of the sequential planning stages. We analyze these enhancements experimentally and show that they can be used to decrease the costs significantly.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Integrated planning; Line planning; Line pool generation; Public transport; Vehicle scheduling